An experimental and theoretical study of the molecular structure and vibrational spectra of iodotrimethylsilane (SiIMe3) - Montejo, Manuel (2006)
The gas-phase molecular structure of iodotrimethylsilane (ITMS) has been determined from electron diffraction data. Infrared and Raman spectra have been completely assigned. The experimental work is supported by ab initio HF and MP2 calculations for the gas-phase structure determination and DFT(B3LYP) calculations, combined with Pulay's SQM method, for the vibrational spectra data. © the Owner Societies 2006.